PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, KEAHLIAN AUDIT, DAN PENGALAMAN TERHADAP AUDIT JUDGEMENT PADA KANTOR AKUNTAN PUBLIK DI MAKASSAR - Anggi, Gina (Patria Artha Journal of Accounting dan Financial Reporting, 2024)
This study aims to determine the effect of pressure obedience, task complexity, auditexpertise, and auditor experience. The research method used descriptive method. Datacollection uses a survey method using a questionnaire. The data of this research is primarydata by distributing questionnaires. The population of this research are auditors who work in Public Accounting Firms in Makassar City. The sample for this research was 33 auditors. The data analysis techniques and methods used in this research use multiple linear regression analysis. The research results show that (1) obedience pressure has a positive effect on audit judgment, (2) task complexity has a positive effect on audit judgment, (3) audit expertise has a positive effect on audit judgment. And (4) experience has a positive effect on audit judgment.